Fate of Abstracts Presented at Annual Meetings of The Society of Thoracic Surgeons from 2015 to 2019 - Valdes, Carlos A; Bilgili, Ahmet; Stinson, Griffin; Sharaf, Ramy M; Sharaf, Omar M; Brennan, Zachary; Jimenez-Contreras, Fabian; Peek, Giles J; Bleiweis, Mark Steven; Beaver, Thomas M; Jacobs, Jeffrey Phillip (The Annals of thoracic surgery, 2025)
Society of Thoracic Surgeons (STS) annual meetings provide opportunities to disseminate cardiothoracic research. We assessed rates of publication of STS abstracts as manuscripts in peer-reviewed journals over five years and determined factors associated with successful publication. The STS "Annual Meeting Archive" was searched online for abstract books from STS annual meetings from 2015-2019. Abstract books were reviewed for information about presented abstracts. A PubMed and Google search was then performed to identify corresponding peer-reviewed journal publications. A total of 1451 abstracts were presented at STS annual meetings from 2015-2019. Overall publication rate of accepted abstracts as manuscripts in peer-reviewed journals was 1097/1451=75.60%. Most published manuscripts were published in The Annals of Thoracic Surgery (750/1097=68.37%). Median duration between abstract presentation and peer-reviewed journal publication was 313[IQR=212.5-458] days. Only 29/1451=2.00% of abstracts won an award, and all 29 of these award-winning abstracts were published as a manuscript. Oral presentation was associated with increased odds of publication compared to poster presentation (OR=1.28[95% CI=1.04-1.71], p=0.021). Median 5-year impact factor of peer-reviewed journals containing these manuscripts was 5.04[IQR=5.04-5.04], and corresponding manuscripts were cited a median of 4[IQR=1-9] times. Overall, 836/1097=76.20% of manuscripts published in peer-reviewed scientific journals had a corresponding North American author. Annual STS meetings are a forum for the presentation of high-quality research. The rate of publication of accepted STS abstracts as manuscripts in peer-reviewed journals is >75%, comparing favorably with national meetings of other surgical societies, and >2/3 of published manuscripts are published in STS's official journal.